PERCUTANEOUS BILIARY DRAINAGE: A REVIEW OF 150 CASES - Mohammad Atif Shiraz (Army Medical College Rawalpindi, 2019)
Objective: To review our technique of ultrasound and fluoroscopically guided Percutaneous Transhepatic Biliary Drainage (PTBD) procedures, and compare our complication rate with internationally accepted standards.